(untitled) (Educational Dimension, 2024)
The editorial board of Educational Dimension, announces the formal retraction of the following article: Lavrentieva, O.O., Rybalko, L.M., Tsys, O.O. and Uchitel, A.D., 2019. Theoretical and methodical aspects of the organization of students’ independent study activities together with the use of ICT and tools. Educational Dimension, 1, pp.27–59. Available from: https://doi.org/10.31812/educdim.v53i1.3831